Analisis Kinerja Pegawai Pada Badan Penyelesaian Sengketa Konsumen (BPSK) Kota Medan - Tanti Juliana; Isnaini Isnaini; Budi Hartono (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The purpose of this study was to analyze and describe the performance of employees and their obstacles at the Medan City Consumer Dispute Resolution Agency (BPSK). The research method used is descriptive using a qualitative method that focuses on the process, description of the analysis. To determine the current performance of the Medan City Consumer Dispute Resolution Agency (BPSK), the researcher chose to use the 5 dimensions of employee performance proposed by Anwar Prabu Mangkunegara, namely work quality, work quantity, work discipline, initiative and responsibility. The quality of work is still low in terms of receiving complaints and consulting. The work quantity has not been maximized. The work discipline of employees has not gone according to what the community expects. Employees have good initiative in carrying out their duties. The responsibility of employees for all aspects related to the tasks carried out is quite good although there are still various improvements that must be made.